Spatial Direction of Minor Rice Land Based on Land Suitability and SWOT Analysis in Tanasitolo District, Wajo District - Nevi kurniawati (Journal of Multidisciplinary Science, 2022)
This study aimed to determine the potential and strategies for mina paddy land management based on land suitability and SWOT analysis in Tanasitolo District, Wajo Regency. The analytical tools used are land suitability analysis and swot analysis. The results of the study show that the potential for managing the mina paddy pattern of aquaculture in Tansitolo District, Wajo Regency, can be developed in the western region of irrigated rice fields. The potential for fisheries management with the Mina paddy pattern can be increased if the availability of irrigation networks increases. The strategy for managing the aquaculture fisheries of the Mina paddy pattern is that the government and the community work together Increase the coordination of all parties to make cheap/economical feed, create cooperation between cultivators and groups and open up easy access to capital, Carry out water quality management and use fish that have a high tolerance for decline water quality, providing quality seeds/parents.